Garść refleksji na temat pierwszego wydania wspomnień Aleksandra Mogilnickiego - Śmiechowski, Kamil (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
Aleksander Mogilnicki (1875–1956) was a lawyer, academic scholar and social activist. Between 1924 and 1929 he was the president of Poland’s Supreme Court, dismissed after his conflict with the government during Sanation period. Mogilnicki’s memoirs, written after the Second World War, were unexpectedly published in 2008 by Mrs. Barbara Izdebska, granddaughter of the author. In spite of numerous editing errors, the memoirs can be a useful historical source. The memoirs contains the interesting information about Łódź in the end of the 19th century and during the Revolution of 1905–1907 in the Kingdom of Poland. The edition also contains a wide description of law-breaking by the government after the 1926 May Coup d’Etat. Mogilnicki’s opinion about Emil Stanisław Rappaport (1877–1965) is a great example of friendship which has turned into a hostilities.